Low‐SES Preschool Children's Eyewitness Memory: The Role of Narrative Skill. (January 2016) - Chae, Yoojin; Kulkofsky, Sarah; Debaran, Francisco; Wang, Qi; Hart, Sybil L.
Abstract : This study investigated the relation between narrative skill and eyewitness memory in young children from low‐socioeconomic status (SES) communities. A total of 176 children aged 3–5 years were interviewed about a conflict event they witnessed. The quality of their narratives about the event and their ability to narrate a story from a picture book were examined in relation to memory of the event. Comprehensive measures of individual differences in vocabulary skill, adaptive language use, and behavioral characteristics were also administered. The results revealed that children who produced longer, more descriptive, and more cohesive narratives about the event recalled more accurate details and made fewer memory errors, independent of their language ability and behavioral characteristics. The quality of story narratives did not make any independent contributions to memory. Child's age was a robust predictor of memory for the event. Implications of the findings for understanding eyewitness memory in low‐SES children are discussed. Copyright © 2016 John Wiley & Sons, Ltd.